Visual Ethnography, Thick Description and Cultural Representation - Kharel, Dipesh (Dhaulagiri Journal of Sociology and Anthropology, 2015)
The purposes of this paper are threefold: to cover historical, theoretical and methodological overview of visual ethnography (photography and film) as a research tool in studying culture; to examine visual ethnography as a means of cultural representation, and to discuss visual ethnographic method with Clifford Geertz’s idea of “thick description”. I hope to bring some clarity and consensus to our understanding how visual ethnography can be an adequate research tool for “thick description” and a study of culture. Furthermore, in this paper, I begin by seeing visual ethnography in the context to visual anthropology, photography, ethnographic film, and semiotics.